MiR-23b-3p promotes postmenopausal osteoporosis by targeting MRC2 and regulating the Wnt/β-catenin signaling pathway - Ran Li; Qing Ruan; Fei Yin; Kunchi Zhao (Journal of Pharmacological Sciences, 2021)
Postmenopausal osteoporosis (PMOP) is one of the most common metabolic bone diseases in postmenopausal women. Increasing evidence has indicated that microRNAs (miRNAs) play vital regulatory roles during osteoporosis progression. This study aimed to investigate the potential function of miR-23b-3p in the osteogenic differentiation of human bone marrow mesenchymal stem cells (hMSCs). PMOP was induced in mice by bilateral ovariectomy. X-ray absorptiometry was applied to detect BMD and BMC in PMOP mice. Luciferase reporter assay and RIP assay were utilized to investigate the relationship between miR-23b-3p and MRC2. We found the upregulation of miR-23b-3p in bone tissues of PMOP mice. Silencing of miR-23b-3p relieved PMOP in mice. Moreover, miR-23b-3p knockdown facilitated the osteogenic differentiation of hMSCs by increasing the expression of Runx2, OCN, Osterix and promoting ALP activity. Mechanistically, MRC2 is a downstream target gene of miR-23b-3p. MRC2 knockdown significantly rescued the promoting effect of lenti-miR-23b-3p inhibitor on osteogenic differentiation of hMSCs. Furthermore, miR-23b-3p targeted MRC2 to inhibit the Wnt/β-catenin pathway during the osteogenic differentiation of hMSCs. In summary, inhibition of miR-23b-3p alleviates PMOP by targeting MRC2 to inhibit the Wnt/β-catenin signaling, which may provide a novel molecular insight for osteoporosis therapy.